THE RELATIONSHIP BETWEEN SUBJECTIVE SLEEP QUALITY AND BLOOD PRESSURE AMONG UNIVERSITY STUDENTS - Lainsamputty, Ferdy; Dotulung, Mutiara Nala Aurelia; Mononutu, Leroy Avron Justin; Pikan, Febi Ruth Alexandra; Lontaan, Maria Kristyani; Wuisang, Metty (Nursing Sciences Journal, 2025)
Poor sleep quality among university students is often associated with academic stress, lifestyle habits, and irregular routines, which may influence blood pressure (BP). This study aimed to examine the relationship between sleep quality and BP in Indonesian university students. A descriptive correlational study with a cross-sectional design was conducted among 207 students at a private university in North Sulawesi Province of Indonesia. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) and BP was measured with an aneroid sphygmomanometer. Data analysis included descriptive statistics and Spearman correlation. The mean sleep quality score was 8.50 (SD=3.51) and 84.1% of participants were classified as having poor sleep quality. The mean systolic and diastolic BP were 107.76 mmHg (SD=13.61) and 75.91 mmHg (SD=11.91), respectively. A significant but weak negative correlation was observed between sleep quality and systolic BP (r=-0.191, p=0.006). While these findings differ from much of the global evidence linking poor sleep to higher BP, they highlight the complexity of sleep-BP interactions in young and healthy populations. These findings emphasize the importance of promoting better sleep hygiene, healthier lifestyle behaviors, and cardiovascular health strategies within university settings.